Organizational factors of career management employed in the transition economy (Vallis Aurea, 2019)
The aim of this research was to determine which organizational factors have an impact on the realization of individual employee career plans. The sample was of a quotient, random selection of the respondent, of the size of 60 examinees (n = 60). It was formed from 20 large organizations from all over Croatia. The survey was conducted by direct survey. The regression analysis method was applied. The regression equation of organizational factors that affects the career development of employees is calculated and determined.Of the six independent variables included, it was established that the most impacted on the career plan of the employees is the analysis and enrichment of the work, followed by psychological monitoring. The lowest coefficient of regression has been shown by career workshops and career charts.